(untitled) (REMUNOM, 2025)
This study’s main objective is to identify the social representations of psychology professionals regarding deaf people. These representations, whether constructed in the social work environment, academic work, or organizational context, are also to understand the variations in socioeconomic interests that permeate the construction of these representations of professionals in their respective fields. The concept of deaf people is constantly changing for improvement and sociopolitical advancement, emphasizing difference rather than disability, considering deaf people and their culture, and can be validated through Libras (Brazilian Sign Language). Despite these advances, there are still ongoing controversies in educational and professional development for these individuals. Given the above, and through a bibliographical study, this study explores the relationships between psychologists, hearing educators, and deaf students, limitations, and inclusion.